PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN DAN KEPUASAN KONSUMEN DALAM MENGGUNAKAN JASA EKSPEDISI PADA PT. SAMAS AGUNG DI SULAWESI TENGAH - Bastun, Moh. Rifki (Katalogis, 2015)
PT. Samas Agung is a shipping expedition company and implements contemporary service marketing system. The management of the company adopts service marketing mix strategies on product, place, price, promotion, people, productivity, and quality, process, and physical evidence. Yet, the operation is still ineffective. Therefore, this research intends to explore service marketing mix and its effect on customers ’ decisions and satisfaction by using Structural Equation Model (SEM). The result indicates a significant influence of product, place, price, promotion, people, productivity and quality, process, and physical evidence on customers ‘ decision; and decision has a significant effect on customers ‘ satisfaction. This study suggests that the results can be used to maintain or improve customers ‘ satisfaction. In addition, the company is required to improve its marketing mix strategy in its policy implementation and market penetration.